Obtención de biocombustible mediante pirólisis con base en el aprovechamiento de residuos agrícolas partiendo de la cascarilla de arroz en los cultivos de la región de Tolima Grande (Tolima y Huila). (2022)
The present work seeks to analyze the environmental feasibility of developing bio-ethanol using an agricultural residue such as rice husk as biomass, through the pyrolysis process. From this investigation, it was found that this residue is a great candidate for biomass, thanks to the amount produced nationally and internationally; to its use and final disposal that is currently given and clearly its composition, which allows a great degradation of biomass in the pyrolysis process. Likewise, the necessary Colombian regulations will be established for the production of bio-oil, and its handling in private vehicle engines with the mixture of ACPM in the different engines, as well as its standardization for an optimal process and use of this product.